Interrelation Between Glacier Summer Mass Balance And Runoff In Mountain River Basins - V. Konovalov; E. Rets; N. Pimankina (Geography, Environment, Sustainability, 2019)
Measurements of summer mass balance Bs, made over the period 1946-2016, on 56 continental glaciers, located in the basins of mountain rivers in 14 countries, were analysed for the purpose of resolving several tasks: (a) constructing physically based interrelations between river flow Wbas and Bs; (b) estimating the representativeness of local measurement of Bs for enhancement of hydrological computations and for control of modelled values Wbas; and (c) use of time series of Bs for the evaluation of norms and extrema of Wbas. Results of the study of the outlined problem serve as the basis for making the transition of local glaciological characteristics to the basin-wide level by using the relationship between runoff and summer balance of glaciers. It includes also analysis and conclusions on the spatial and temporal homogeneity of averaging glaciological mass balance data by the sampling method.